Encyclopedia of sensors and biosensors - Narayan, Roger (Elsevier, 2023)
Encyclopedia of Sensors and Biosensors, Four Volume Set provides unique foundational level information on the rapidly growing sensor community. The book covers innovations in materials, designs, devices and software that find their way into new types of sensors. Sections include over 1000 color images, including representations of sensor design, sensor manufacturing, and assessments of sensor performance. In addition, applications of sensors in healthcare, food safety, environmental engineering and other fields are discussed, making this a truly interdisciplinary work. The book is structured using a logical and thematic approach, with chapters taking a balanced viewpoint, listing both advantages and disadvantages. Perfect for those learning their trade in both academia and industry, this vital reference work will serve many groups, including chemists, engineers, biological scientists, clinicians, and industrial researchers.